The Evolution of Strategic Planning in the Republic of Uzbekistan (From the Post-Soviet Period to Innovative and Digital Transformation) - Usmanbekovna, Sharipova Guzal (Web of Scientist International Scientific Research Journal, 2025)
This paper presents a retrospective trend-oriented analysis of the Republic of Uzbekistan's experience in developing and implementing national and regional development strategies. The relevance of the study is due to the dynamic structural, innovative and market transformations in the country associated with digitalisation, the introduction of new technologies and the transition to indicative methods of regulation. The aim is to provide a comprehensive analysis of economic development in the context of digital transformation, liberalisation and democratisation reforms, as well as to identify best practices for modernising industries to enhance global competitiveness. The paper examines the stages of the post-Soviet transition, key strategies (Action Strategy 2017–2021, Uzbekistan 2030, Innovation Development Strategy 2022–2026), territorial planning methodology, investment policy, and the development of light industry, renewable energy and digital technologies. Based on empirical data, macroeconomic shifts, regional disparities and the effectiveness of reforms are analysed. The conclusions emphasise the need for further improvement of institutional mechanisms, human capital and innovation drivers for sustainable growth.